1993
DOI: 10.1128/jcm.31.10.2777-2779.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of multiple species of vancomycin-resistant enterococci, including an evaluation of Vitek software version 7.1

Abstract: A total of 374 clinical isolates ofEnterococcus spp. were characterized to determine the species distribution and vancomycin resistance. The ability of the Vitek system (bioMerieux Inc, Hazelwood, St. Louis, Mo.) to identify enterococci to the species level and to recognize vancomycin resistance by using computer software version 7.1 was evaluated. Conventional methods were used for identification and agar dilution was used for susceptibility testing, the results of which were as follows (presented as number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Several studies have evaluated the abilities of commercial and reference antimicrobial susceptibility testing methods to detect vancomycin resistance in Enterococcus isolates (3,(9)(10)(11)(12)(13)(14)(15)(16). Those studies which have evaluated current versions of automated or semiautomated commercial systems, such as the Vitek system (bioMerieux, Inc.), the MicroScan Rapid system (Baxter Health Care Corp., West Sacramento, Calif.), or the Alamar MIC system (Alamar Biosciences, Sacramento, Calif.), have shown that these methods do not reliably detect vancomycin resistance in enterococci (11,13,15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the abilities of commercial and reference antimicrobial susceptibility testing methods to detect vancomycin resistance in Enterococcus isolates (3,(9)(10)(11)(12)(13)(14)(15)(16). Those studies which have evaluated current versions of automated or semiautomated commercial systems, such as the Vitek system (bioMerieux, Inc.), the MicroScan Rapid system (Baxter Health Care Corp., West Sacramento, Calif.), or the Alamar MIC system (Alamar Biosciences, Sacramento, Calif.), have shown that these methods do not reliably detect vancomycin resistance in enterococci (11,13,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of all of the above studies may be the inconsistent definition for the "gold standard" or reference susceptibility result. Some investigators have compared test results of the study method to a broth dilution result (11,13), while others have compared the results of the study method to results obtained by using either agar dilution (9,14), disk diffusion (15), the Micro Scan Rapid method (15,16), or E-test method (12) or by comparing results to the vancomycin resistance genotype (3,10,11). Furthermore, for two of these studies, evaluations were limited to Enterococcus isolates with high-level vancomycin resistance (3,12).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to accurately identify enterococci at the species level is important not only for epidemiological purposes but also to recognize species such as E. faecium and the motile enterococci, which tend to show resistance to antimicrobial agents commonly used for therapy. Automated systems, such as the Vitek system and both the conventional and rapid Mi-croScan systems, are reported to provide accurate identification for both E. faecalis and E. faecium; however, they are not considered reliable for the identification of the other Enterococcus species (1,2,18,24,26). In addition, using automated systems to perform susceptibility testing of enterococci for antimicrobial agents, such as ampicillin, vancomycin, and the aminoglycosides, has had conflicting results (13, 21-23, 26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Automated systems, including the Vitek and MicroScan systems, have been developed to identify and to determine the antimicrobial susceptibility of enterococci (1,2,18,22,23,(25)(26)(27)(28). Previous studies have shown conventional MicroScan panels to be reliable in the identification of Enterococcus spe-cies, even though the data bank includes only E. faecalis, E. faecium, E. durans, and E. avium (24).…”
mentioning
confidence: 99%
“…Given the widespread and rapidly evolving resistance patterns, empirical therapy of enterococcal infection is no longer tenable, and it is essential that clinical laboratories be able to rapidly and reliably detect antimicrobial‐resistant isolates. Previous studies have documented the inadequacy of automated susceptibility products, some broth microdilution (BMD) systems and the standardized disk diffusion test interpretive criteria [7,13–17]. In response to these problems.…”
Section: Vancomycin Minimum Inhibitory Concentrations (Mics) Measuredmentioning
confidence: 99%